DAMPAK PERILAKU SOSIAL TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN PAI DAN BUDI PEKERTI DI SDN PEKIRINGANKOTA CIREBON - Iyan Nopiyanto; Jamali Sahrodi; Septi Gumiandari (CV. ADIBA AISHA AMIRA, 2025)
Education is one of the crucial aspects in human life as it can elevate the dignity of individuals. Furthermore, education plays a pivotal role in shaping individuals into virtuous beings. The aim of this research is to investigate the impact of social behavior on students' academic achievement in Islamic Education (PAI) and Character Education at Pekiringan Elementary School in the city of Cirebon. This research falls under the category of quantitative research. The population consists of 30 students from grades 4-6 at Pekiringan Elementary School in the city of Cirebon. The sampling technique employed is exhaustive sampling, where the entire population is taken as the sample. Therefore, the total sample size for this study is 30 students. The data analysis technique used is hypothesis testing through the Spearman rank correlation test. The research findings indicate that social behavior influences students' academic achievement in the subjects of PAI and Character Education at Pekiringan Elementary School in the city of Cirebon.